Presenting a model of factors affecting social unrest and its effect on observing behavioral norms in stadiums - Masoud Naderian jahromi; Elham Akhavan (Islamic Azad university, Isfahan Branch, 2022)
Objective: In order to provide a comprehensive and coherent view of social turmoil, the purpose of this study was to design a multilevel model of social turmoil and its effect on the observance of behavioral norms in stadiums.Methodology: The research was applied in terms of purpose and mixed in terms of implementation method (qualitative and quantitative). The statistical population of the research in the first part included existing and available research in valid scientific databases in the field of social turmoil and in the second part was the spectators and managers of football clubs in 1398. Sampling was performed by purposive and available methods. The identification of the desired factors was done by meta-combination method and determining the relationships between them with the help of interpretive structural modeling.Results: The results showed social turmoil at four social levels (global developments and cultural transition, lack of justice in resource distribution, culture industry and lack of agreement on the fundamental values of society), organizational level (base incompatibilities, functional inconsistency of community institutions, non-legislative Necessary and weak (lack of necessary structures), group (ethnicity and sports teams, politicians entering the field of sports, informal groups) and individual level (personal characteristics, family history, lack of self-management, internal and external motivation, economic poverty) was classified. The results also showed that there is a statistically significant inverse relationship between the two variables of feeling social turmoil and the degree of observance of spectator behavioral normsConclusion: Managers of clubs and stadiums should consider legal facilities for sports spectators as good citizens. The People's Police should be formed by the fan club from among the spectators and the necessary preparations should be made for each match by the officials, and they should make careful and appropriate plans before the match in accordance with the rules and standards.Considering the results of the research which showed that the more control and the possibility of punishment for the norm-breakers, the more the development of the principles of fair play increases and the more the beauty of the sport and its enjoyment, so it is suggested that Sports clubs should be organized in a systematic manner and have a serious and effective participation in the development of a moral charter in accordance with the cultural conditions of Iranian society. It is also suggested that spectator rights in sports environments, both before and during competitions, in which the behavioral, verbal and behavioral indicators of officials and police with spectators are precisely defined and to train it through training sessions. Hold public events and workshops. It is suggested that during a systematic and continuous process, good and law-abiding spectators be identified and encouraged through the fan club, and that the managers of clubs and stadiums consider facilities for sports spectators as good citizens according to the law. It is suggested that the People's Police be formed by the fan club from among the spectators and that the necessary preparations be made for each match by the officials, and that they make careful and appropriate plans before the match in accordance with the rules and standards. Win-lose thoughts are not encouraged as much as possible by coaches, managers and players, and the nature of sports participation and enjoyment of the match is promoted.